Different cytokine patterns in bronchial biopsies in asthma and chronic bronchitis - Mueller, R.; Chanez, P.; Campbell, A.M.; Bousquet, J.; Heusser, C.; Bullock, G.R. (Respiratory medicine, 1996)
Bronchial biopsies have made possible the detailed study of the pathology of the airways of humans with respiratory disease. Much data has been accumulated on asthmatics or normal controls but much less is known about chronic bronchitics. The aim of this study was to characterize the cellular and cytokine pattern seen in chronic bronchitics and to compare these with control and asthmatic subjects. The patients were also characterized clinically. In this study, immunocytochemistry on cryostat sections from bronchial biopsies were used to determine the level of inflammatory cells and cells of the immune system as well as the pattern of cytokines. This study revealed a distinct cellular and cytokine pattern for each of the three different patient groups, although the diversity of the cytokines analysed was limited by the size of the biopsies. In the inflammatory infiltrate of patients with asthma, CD4+ T-cells and eosinophils were the most prominent cell types discerned. All of the expected cytokines such as IL-1, TNF-α, IL-4, IL-5 and IFN-γ were found. In contrast, the emphasis in chronic bronchitic patients was quite different. The predominant cell types were macrophages, neutrophils, mast cells and CD8+ T-cells, but eosinophils were also abundant. In addition, IL-4 and TNF-α were the only cytokines present of those tested.